2016
DOI: 10.1021/acs.accounts.6b00343
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Self-Assembly of Hairy Inorganic Nanoparticles

Abstract: Current interest in functional assemblies of inorganic nanoparticles (NPs) stems from their collective properties and diverse applications ranging from nanomedicines to optically active metamaterials. Coating the surface of NPs with polymers allows for tailoring of the interactions between NPs to assemble them into hybrid nanocomposites with targeted architectures. This class of building blocks is termed "hairy" inorganic NPs (HINPs). Regiospecific attachment of polymers has been used to achieve directional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 59 publications
0
83
0
Order By: Relevance
“…Selfassembly is a promising strategy for generating highly ordered nano-and microstructured homo(hetero)structures, which can provide more interfacial contact among components. 12,13 In this study, for the first time the originally inert PANI is converted into a highly active electrocatalyst with good stability for hydrogen evolution by interfacial electronic coupling with properly engineered metal oxides with highly ordered assembly architecture. For example, the as-synthesized WO 3 assemblies@PANI exhibits the lowest overpotential (74 mV) at 10 mA·cm −2 in 0.5M H 2 SO 4 electrolyte.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selfassembly is a promising strategy for generating highly ordered nano-and microstructured homo(hetero)structures, which can provide more interfacial contact among components. 12,13 In this study, for the first time the originally inert PANI is converted into a highly active electrocatalyst with good stability for hydrogen evolution by interfacial electronic coupling with properly engineered metal oxides with highly ordered assembly architecture. For example, the as-synthesized WO 3 assemblies@PANI exhibits the lowest overpotential (74 mV) at 10 mA·cm −2 in 0.5M H 2 SO 4 electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…However, other controllable interfacial electronic coupling to activate the nonmetal atoms between the support and active component remains a great challenge. Self‐assembly is a promising strategy for generating highly ordered nano‐ and microstructured homo(hetero)structures, which can provide more interfacial contact among components …”
Section: Introductionmentioning
confidence: 99%
“…Notably, self‐assembly of PNC‐polymer hybrid building blocks is able to generate single PNC with tailored internal structures (e.g., core–shell, core–gap–shell), or integrate PNCs into higher dimensional ensembles (i.e., cluster, nanochain, vesicle), which often lead to strong interparticles/intraparticle plasmonic coupling . Such coupling can induce significant red‐shifts in LSPR spectra and create greatly enhanced electromagnetic fields, both of which endow plasmonic assemblies with dramatically different optical properties compared to single PNC counterparts …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there are a number of benefits in conjugating polymers with PNCs to direct their self‐assembly: i) The conformation transformation of polymer chains provides the driving force for self‐assembly . For example, the amphiphilic single‐component or mixed polymer brushes anchored onto the PNCs can afford amphiphilicity‐driven self‐assembly to produce a library of assemblies including core–shell structure, Janus nanoparticles (JNPs), nanocluster, nanochain, lamellae, and vesicle.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of organic polymers with inorganic materials in a competitive and promising way can remarkably alter the practical performance like chemical, mechanical, optical, electrical, rheological, and surface properties 19, 20, 21. Therefore, the incorporation of inorganic nanoparticles into the membrane can endow the generated proteinosomes with some advanced inorganic nanoparticle functionalities (e.g., luminescent, magnetic, and catalytic properties) 22, 23. Santhosh et al reported fluorescence nanoclusters (NCs) using human serum albumin stabilized gold for sensitive and reliable detection of free bilirubin in blood serum samples 24.…”
mentioning
confidence: 99%